Analysing falls in coronary heart disease mortality in the West Bank between 1998 and 2009. Issue 4 (24th August 2012) - Abu-Rmeileh, Niveen M E; Shoaibi, Azza; O'Flaherty, Martin; Capewell, Simon; Husseini, Abdullatif
Abstract : Objectives: To analyse coronary heart disease (CHD) mortality and risk factor trends in the West Bank, occupied Palestinian territory between 1998 and 2009. Design: Modelling study using CHD IMPACT model. Setting: The West Bank, occupied Palestinian territory. Participants: Data on populations, mortality, patient groups and numbers, treatments and cardiovascular risk factor trends were obtained from national and local surveys, routine national and WHO statistics, and critically appraised. Data were then integrated and analysed using a previously validated CHD model. Primary and secondary outcome measures: CHD deaths prevented or postponed are the main outcome. Results: CHD death rates fell by 20% in the West Bank, between 1998 and 2009. Smoking prevalence was initially high in men, 51%, but decreased to 42%. Population blood pressure levels and total cholesterol levels also decreased. Conversely, body mass index rose by 1–2 kg/m 2 and diabetes increased by 2–8%. Population modelling suggested that more than two-thirds of the mortality fall was attributable to decreases in major risk factors, mainly total cholesterol, blood pressure and smoking. Approximately one-third of the CHD mortality decreases were attributable to treatments, particularly for secondary prevention and heart failure. However, the contributions from statins, surgery and angioplasty were consistently small. Conclusions: CHD mortality fell by 20% between 1998 and 2009 in the West Bank. More than two-third of this fall was due to decreases in major risk factors, particularly total cholesterol and blood pressure. Our results clearly indicate that risk factor reductions in the general population compared save substantially more lives to specific treatments for individual patients. This emphasizes the importance of population-wide primary prevention strategies.